Axonal injury is a targetable driver of glioblastoma progression - Melanie Clements; Wenhao Tang; Zan Florjanic Baronik; Holly Simpson Ragdale; Roger Oria; Dimitrios Volteras; Ian J. White; Gordon Beattie; Imran Uddin; Tchern Lenn; Rachel Lindsay; Sara Castro Devesa; et al. (Nature, 2025)
Abstract Glioblastoma (GBM) is an aggressive and highly therapy-resistant brain tumour 1,2 . Although advanced disease has been intensely investigated, the mechanisms that underpin the earlier, likely more tractable, stages of GBM development remain poorly understood. Here we identify axonal injury as a key driver of GBM progression, which we find is induced in white matter by early tumour cells preferentially expanding in this region. Mechanistically, axonal injury promotes gliomagenesis by triggering Wallerian degeneration, a targetable active programme of axonal death 3 , which we show increases neuroinflammation and tumour proliferation. Inactivation of SARM1, the key enzyme activated in response to injury that mediates Wallerian degeneration 4 , was sufficient to break this tumour-promoting feedforward loop, leading to the development of less advanced terminal tumours and prolonged survival in mice. Thus, targeting the tumour-induced injury microenvironment may supress progression from latent to advanced disease, thereby providing a potential strategy for GBM interception and control.